Understanding Turkish Rhetoric in the Intertextuality of Two Seminal Texts: The Orkhon Inscriptions and Atatürk's Nutuk. Issue 2 (4th May 2019) - Guler, Elif; Goksel, Iklim
ABSTRACT: This study contributes to the conversations on a more globalized and inclusive rhetorical praxis by focusing on how rhetoric was produced and understood by Turks – a group whose history spans centuries since their ancient origins in central Asia. We examine the ways in which Turkic/Turkish rhetoric was practiced and conceptualized in two seminal texts from the pre-Islamic and republican periods of the Turkish rhetorical tradition: the Orkhon inscriptions (8th century) and Atatürk's Nutuk (1927). The intertextuality of these texts allows us to explore their relationships across time and space as well as mediate rhetorical styles and performances in their discourse.